Analysis of Spinal Electromyography Signal When Lifting an Object - B. Bahar, M; A. Zainal, S; W. Too, J; F. Miskon, M; I.A. Apandi, N; L.A. Shaari, N; M.S.M. Aras, M; Ali, F (International Journal of Engineering and Technology, 2018)
Lifting and swinging are daily activities that human do using the spine. Furthermore, spine provides support during standing and walking. Therefore, it is very important in everyday activities and it will be inconvenient when it is injured. Technology has provided ways to machine and human integration in helping or supporting people in their daily tasks. To make this integration successful, machines or robots need to understand the human muscle activity. To do so, electromyography (EMG) a bio signal record the electricity generated by muscle was implemented. However, the signal often influenced by the unwanted noise. In this paper, the MVC normalization method is applied to determine the spinal EMG signal on lumbar multifidus muscle when lifting an object. In order to analyze the identity of spinal EMG signal, two statistical analyses are done; 1) ANOVA analysis and 2) Boxplot analysis. The signal will go through 8th order Gaussian function or Exponential Weight Moving Average Filter before being analysed. Results show that Exponential Weight Moving Average Filter gives more consistent value compared to 8th order Gaussian function which is 0.0428V RMSE based on linear fitting done from the maximum amplitude gather from the boxplot analysis done.Â Â